Analysis of rare fusions in NSCLC: genomic architecture and clinical implications - Şeker-Cin, Huriye; Tay, Timothy Kwang Yong; Kazdal, Daniel; Kluck, Klaus; Ball, Markus; Neumann, Olaf; Winter, Hauke; Herth, Felix; Heußel, Claus Peter; Savai, Rajkumar; Schirmacher, Peter; Thomas, Michael; et al. (Lung cancer, 2023)
Objectives - Molecular diagnosis for targeted therapies has been improved significantly in non-small-cell lung cancer (NSCLC) patients in recent years. Here we report on the prevalence of rare fusions in NSCLC and dissect their genomic architecture and potential clinical implications. - Materials and Methods - Overall, n = 5554 NSCLC patients underwent next-generation sequencing (NGS) for combined detection of oncogenic mutations and fusions either at primary diagnosis (n = 5246) or after therapy resistance (n = 308). Panels of different sizes were employed with closed amplicon-based, or open assays, i.e. anchored multiplex PCR (AMP) and hybrid capture-based, for detection of translocations, including “rare” fusions, defined as those beyond ALK, ROS1, RET and <0.5 % frequency in NSCLC. - Results - Rare fusions involving EGFR, MET, HER2, BRAF and other potentially actionable oncogenes were detected in 0.5% (n = 26) of therapy-naive and 2% (n = 6) TKI-treated tumors. Detection was increased using open assays and/or larger panels, especially those covering >25 genes, by approximately 1-2% (p = 0.001 for both). Patient characteristics (age, gender, smoking, TP53 co-mutations (56%), or mean tumor mutational burden (TMB) (4.8 mut/Mb)) showed no association with presence of rare fusions. Non-functional alterations, i.e. out-of-frame or lacking kinase domains, comprised one-third of detected rare fusions and were significantly associated with simultaneous presence of classical oncogenic drivers, e.g. EGFR or KRAS mutations (p < 0.001), or use of larger panels (frequency of non-functional among the detected rare fusions 57% for 25+ gene- vs. 12% for smaller panels, p < 0.001). As many rare fusions were identified before availability of targeted therapy, mean survival for therapy-naïve patients was 23.8 months, comparable with wild-type tumors. - Conclusion - Approximately 1-2% of advanced NSCLC harbor rare fusions, which are potentially actionable and may support diagnosis. Routine adoption of broad NGS assays capable to identify exact fusion points and potentially retained protein domains can increase the yield of therapeutically relevant molecular information in advanced NSCLC.